Anion Doping: A New Strategy for Developing High‐Performance Perovskite‐Type Cathode Materials of Solid Oxide Fuel Cells. Issue 17 (16th May 2017) - Zhang, Zhenbao; Zhu, Yinlong; Zhong, Yijun; Zhou, Wei; Shao, Zongping
Abstract : Overcoming the sluggish activity of cathode materials is critical to realizing the wide‐spread application of intermediate‐temperature solid oxide fuel cells. Herein, a new way is reported to tune the performance of perovskite‐type materials as oxygen reduction electrodes by embedding anions (F − ) in oxygen sites. The obtained perovskite oxyfluorides SrFeO3− σ − δ F σ and SrFe0.9 Ti0.1 O3− σ − δ F σ (σ = 0.05 and 0.10) show improved electrocatalytic activity compared to their parent oxides, achieving area specific resistance values of 0.875, 0.393, and 0.491 Ω cm 2 for SrFeO3− δ, SrFeO2.95− δ F0.05, and SrFeO2.90− δ F0.10, respectively, at 600 °C in air. Such improved performance is a result of the improved bulk diffusion and surface exchange properties due to anion doping. Moreover, favorable stability in performance is also demonstrated for the F − anion‐doped perovskites as oxygen reduction electrodes at 650 °C for a test period of ≈200 h. A combination of anion doping and cation doping may provide a highly attractive strategy for the future development of cathode materials. Abstract : A novel and facile strategy toward the development of a high‐performance cathode is proposed for the first time to resolve the slow activity of cathode materials by embedding anion ions into the perovskite lattice for intermediate‐temperature solid oxide fuel cells.